Edukasi tentang Kehamilan Usia Remaja dan Berbagai Permasalahannya di Puskesmas Putri Ayu - Kusuma, Ratu; Hesty, Hesty; Sari, Mila Triana; Ariyanto, Ariyanto (Jurnal Abdimas Kesehatan (JAK), 2025)
Teenage pregnancy is one of the health problems in Indonesia, Riskesdas 2018 recorded 2,867 teenage pregnancies (10-19 years) and 15 of them were aged 10-14 years. BPS Indonesia reported that the average birth rate for teenagers in 2018 was 36/1,000 births and in Jambi Province 46/1,000 births (national target 18/1000 births). Based on the Medical Records of the KIA Polyclinic and interviews with the Midwife Coordinator of the KIA Program and the PKPR Program, it is known that in recent years there has been an increase in teenage pregnancies. In 2020 (33 cases), 2021 (33 cases), 2022 (35 cases), 2023 (31 cases) and 1 of them occurred at the age of 15 years. Interviews were also conducted with 2 teenage mothers who made antenatal visits. First mother: 19 years old, has 2 children, is currently pregnant with her 3rd child from her 2nd husband, and shows symptoms of depression; and second mother: 18 years old, 38 weeks pregnant, has anemia and suffers from hepatitis. Educational activities were carried out in 2 places (December 1, 2023 at the Putri Ayu Health Center Hall and January 20, 2024 at the Asfalis Posrem RT 17, Solok Sipin Village) for 14 teenage mothers, through group education for 60-70 minutes, with a lecture discussion and question and answer method. Before the material was given, leaflets were first distributed to each participant. The delivery of the material used ppt and loudspeakers, before and after education, a pretest and posttest were carried out using the same questionnaire. It was concluded that teenage pregnancy is increasing, while teenagers do not yet have good behavior in preventing it.